Relevansi Kebijakan Fiskal Syariah dalam Mendorong Stabilitas Ekonomi Umat: Kajian Tafsir Tematik Ayat dan Hadis Berbasis Pendekatan Kontemporer - Febi Alicia; Nurhayati; Yenni Samri Juliati Nasution (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the relevance of sharia fiscal policy to the economic stability of the Muslim community through a thematic interpretation of verses and hadiths and a contextual analysis of modern fiscal policy. The study employed qualitative methods, examining literature selected based on criteria such as academic credibility, publisher reputation, publication recency, and relevance to sharia fiscal issues. The analysis was conducted through thematic coding of key issues such as zakat distribution, the role of sukuk in macroeconomic stabilization, and strengthening ZISWAF regulations. The results indicate that sharia fiscal instruments such as zakat, infaq, sadaqah, waqf, and sukuk have a strong normative basis and play a significant role in supporting distributive justice and economic stability. The integration of sharia principles into modern fiscal policy can be an alternative economic mechanism that is fairer and oriented towards the public good. This study is limited by the lack of empirical data; therefore, further research is recommended using a quantitative approach and comparative studies to measure the effectiveness of sharia fiscal policy in a broader context.